(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
English is an extremely important tool for people to communicate with each other. It is not only a means of conveying thoughts and ideas, but also builds friendships, economic relationships and cultural and social relationships. Surely learning writing will help learners develop themselves, their minds and their personalities. Despite its importance, many students face significant challenges in developing effective writing skill. The research aimed to find some errors then suggested methods to help students improve English writing skill. This research was supported with participation of 41 freshmen who are in English class at Tay Do University. Questionnaire, pretest and posttest were the instruments. Participants were asked to write a paragraph in pre-test and post-test. Besides, they also answered questionnaire. The results showed students’ opinions about writing skill; they also gave some difficulties in writing (vocabulary, ideas and grammar) and some improving methods (doing exercises, reading books, discuss with others, and so on) through the questionnaire.